DAI'S STRATEGY TO BUILD THE POLITICAL IMAGE OF CANDIDATES IN THE 2015 MEDAN MAYOR ELECTION - Abdullah, Abdullah; Katimin, Katimin; Susanto, Joko (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2020)
This study aims to explain how the existence of dai in building the political image of candidates in the 2015 Medan Mayor election. Furthermore, the researcher specifically wants to reveal the involvement of dai in the 2015 Medan Mayor election, his motivation to be involved in the Mayor election, the strategy in building candidate imagery, and dai communication ethics in building candidate image in Mayor's election. This research is a political communication research using qualitative research methods. The data collection technique is done by interview, observation, and documentation. Research informants were selected through the snowball technique. The data obtained were then processed using Miles and Huberman, namely through three steps, first reducing data, presenting data, and finally drawing or verifying conclusions. The results of this study indicate that the involvement of the dai in the 2015 election for the mayor of Medan, there were dai who supported the candidate directly, who supported indirectly, the dai group who were neutral and the dai group who refused. The motivation for dai's involvement is based on the motive of power and the motive for personal and group gain. The strategy used in building a candidate's image is carried out by caring for the candidate's character by presenting candidates at religious events, accompanying candidates at religious events, appearing on the candidate's campaign stage, and explaining the candidate's vision and mission to the congregation. Furthermore, the strategy is carried out by packaging political messages in an informative and persuasive manner with an approach that is of appeal, emotional appeal, and reward appeal. The media used by dai as a candidate imaging tool is direct media (face to face) individually or in groups. Also, printed media (newspapers, brochures, bulletin) and new media are used, namely the website, WhatsApp and Facebook. In political imaging activities, Dai still seems to ignore the ethical values of communication, namely, he is still carrying out black campaigns and is inconsistent between words and deeds.